KINERJA OPERASI DAN KINERJA SAHAM PADA PERUSAHAAN NON-KEUANGAN YANG MELAKUKAN DIVESTASI - Noor Sekar Mentari; Amrie Firmansyah (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2019)
Abstract: This study aims to review the operating performance and performance of company shares before and after divestment. Divestment is a financial restructuring carried out by the companies. This study uses liquidity ratios, capital structure ratios, profitability ratios, and market value ratios in analyzing the impact of divestment on the company's operating performance and stock. The research method used in this study is a quantitative method. The object of this research is the non-financial companies that divested and are listed on the Indonesia Stock Exchange (IDX) in 2011 - 2016. Based on the data selection, the companies that became the sample of this study are 5 companies. The selection criteria for the five companies are financial statements available two years before and after divestment, complete and clear financial statement information, stock information, and divestment information. The results showed that divestment in the form of divestment of shares, assets, and spin-offs could affect the impact of the company's operations and shares. Divestment, in general, does not help companies in increasing company liquidity and market value, but divestment improves capital structure and profitability.  Keywords: divestment, operating performance, stock performance.